Phytochemical Analysis of Bioactive Extracts and Seed Oil of Three Euphorbia Species from Algerian Flora by LC-MS and GC-MS - Nadia Toudert; Farida Zakkad; Noureddine Dadda; Abdelouaheb Djilani; Amadou Dicko; Salah Eddine Djilani (Indonesian Journal of Chemistry, 2021)
Euphorbia species possess pharmacological properties that have been widely used for medical purposes worldwide. In this paper, three plants belonging to the Euphorbia genus growing in North-East of Algeria were studied. The phenolic contents were identified using LC-MS, while the fatty acid composition of their fixed oils was determined with GC-MS. The quantification of the total condensed tannins and the leaves' entire anthocyanin content were performed using photometric methods. The main constituents of the polyphenolic compounds identified by LC-MS were ascorbic, chlorogenic, and ellagic acids. The oil yield of the seeds of E. terracina, E. biumbellata, and E. dendroides was 17.48%, 18.5%, and 20.05%, respectively. Quantitative analyses of these oils using GC-MS showed variations in the species' fatty acid constituents' concentrations and compositions. Besides, the phytochemical screening results showed that E. terracina possessed a high amount of tannin and anthocyanin content compared with other studied plants.